2022
DOI: 10.1007/s12662-022-00833-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic postural control and physical stress: an approach to determining injury risk in real sporting conditions

Abstract: Dynamic postural control is one of the essential factors in situations where non-contact injuries mainly occur, i.e., landing, cutting, or stopping. Therefore, testing of dynamic postural control should be implemented in injury risk assessment. Moreover, non-contact injuries mainly occur under loaded conditions when the athlete is physically stressed. Therefore, risk factors and mechanisms of these injuries should also be regarded under loading conditions and not only when the athlete is recovered. Current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These findings indicate that the legs were possibly stressed equally due to both types of physical load, which seems not surprising concerning the symmetric/cyclic nature of the chosen loading protocols. However, it must be considered that the normalized reach distances were only decreasing after cycling but not after running (Heil and Büsch, 2022). Therefore, future studies should also take potentially upcoming differences in the internal load between different load types into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that the legs were possibly stressed equally due to both types of physical load, which seems not surprising concerning the symmetric/cyclic nature of the chosen loading protocols. However, it must be considered that the normalized reach distances were only decreasing after cycling but not after running (Heil and Büsch, 2022). Therefore, future studies should also take potentially upcoming differences in the internal load between different load types into account.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was based on a study by Johnston et al (2018) that was adapted and systematically replicated. The recorded data was analyzed in different studies considering different aspects (Heil et al, 2020b;Heil and Büsch, 2022). The whole project was conducted in accordance with the Declaration of Helsinki, and the local Ethics committee approved the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown a strong relation between poor movement quality of the trunk and the lower limbs (such as misalignment, excessive movement and imbalances 2,3 ) and joint overload 4,5 . Additionally, another essential factor in situations where non-contact injuries mainly occur is the dynamic postural control 6 . Considering that the incidence of non-contact injuries in sport is high, there is a need for appropriate approaches for training and reducing injury risks.…”
Section: Introductionmentioning
confidence: 99%